Modelagem matemática da separação de nanopartículas em campo elétrico - Borges, Lucas Camargos (2020)
In recent decades, has been a growing interest in study of nanotechnology applied to engineering systems and related fields. This is due to numerous applications that can be developed, including employment in chemical and pharmaceutical industries, in separation processes and in different fields of medicine. Thus, characterizing a nanoparticle stream with respect to its particle size distribution has fundamental importance in order to understand how they may interfere with people's daily lives. For this purpose, one of the used devices is the Differential Mobility Analyzer (DMA). In general, DMA is based on electric mobility technique, which consists in separating charged particles with a certain charge when crossing a specific electric field. Thus, for each particle size running through the equipment, a different profile is observed, and only particles with a certain size range will be collected in the DMA classification slit, obtaining a monodisperse aerosol stream from a polydisperse stream at the equipment entrance. The main objective of this study is to propose a systematic methodology for the characterization of the aerosol flow at entrance of two DMAs equipment, designed and built at FEQUI/UFU, by formulating and solving an inverse problem using the Differential Evolution (DE) algorithm. For this, the experimental data reported by Gomes (2018) and Camargo (2019) for different saline concentrations in polydispersed aerosol were considered, which were treated using methodologies present in literature, as well as new approaches proposed in this study. The results showed that the DMA devices used could be treated by the proposed models, identifying the potential of these devices to be adopted as an alternative to commercial equipment; as well as the convergence potential of the DE tool for the same solution from different runs. In addition, one of the adopted models showed the ability to estimate the particle size distribution for a given inlet aerosol intermediate concentration from information of two other concentrations.